Hubungan Self-Esteem dengan Workplace Bullying pada Karyawan PT. X di Kota Padang - Khairiyah, Ummil; Dena, Ilham Bagus; Dewinda, Herio Rizki (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Human resources are important in a company. Companies generally employ employees according to their respective capacities. Being an employee requires someone to adapt in the workplace, because they are sometimes placed in various divisions that require cooperation and good relationships with other people. However, workplace bullying also often occurs by co-workers or other seniors, so this is an important thing that must also be paid attention to, because it can hinder many things, including the performance of employees who experience this. This research aims to determine the relationship between self-esteem and workplace bullying employees in PT. X in Padang City. The independent variable in this research is self-esteem while the dependent variable is workplace bullying. The measuring instruments used in this research are the self-esteem scale and the workplace bullying scale. The sampling technique in this research used a saturated sampling technique. The sample in this research was 108 employees of the company. Validity and reliability testing in this research used the Cronbach's Alpha technique. The validity coefficient results on the self-esteem scale move from rix=0.327 to rix=0.783 with a reliability coefficient value of α=0.914, while the validity coefficient results on the workplace bullying scale move from rix=0.393 to rix=0.782 with a reliability coefficient value of α=0.927 . Based on data analysis, a correlation value of -0.663 was obtained with a significance level of 0.000, which means the hypothesis was accepted. This shows that there is a strong and significant relationship between self-esteem and workplace bullying employees in PT. X in the city of Padang.